Assessment of psychosocial domain of quality of life for women who had undergone hysterectomy - mohammed, Atiya; Abdul-Amir, fatin (Iraqi National Journal of Nursing Specialties, 2005)
Abstract A descriptive (cross sectional) study was conducted to assess psychosocial domain of quality of life for (100) women who had hysterectomy for non malignant indications during 6-12 months post operative. The study carried out in both consultation clinics of Al-Elwiya Maternity Hospital and Baghdad Teaching Hospital from January 5th 2003 to July 10th 2003). The results of the study show that hysterectomy achieved a highly successful outcome in terms of psychological and social adjustments for hysterectomies women, a highly significant differences between quality of life (QoL) and some of demographic characteristics. Age was the best significant predictor of psychosocial outcome. The study recommended an education programs should be developed for women and their partners, and provision of concerned pamphlets books. Further research that confirm the present data with a large number of women is required.